BER Analysis over Weibull-Gamma and Mixture-Gamma Fading Channels under SC Scheme in Presence of GGD Noise for Nano Communication System - Gupta, Akanksha (My University, 2019)
A completely new paradigm of communication known as Nano communication (NC) is making it’s place among the researchers very fast. NC has become an established research field and enables numerous new solutions in almost every field. Targeted Drug delivery system, Air pollution control, Food management, Nuclear Biological and Chemical (NBC) defense are few vital applications among others. Further, various researchers are working on real time application of NC around the world. However, for real time wireless system, the impairments which need to be focused are fading and noise. According to literature, the most suitable fading channels for EMNC under CM1 scenario are Weibull-Gamma and Mixture-Gamma that includes both shadowing and fading for NC. Also, GGD has been considered as most appropriate noise for NC under CM1 scenario. It is not only provided various noise models as its special case but also most suitable for operating over physical conditions of NC. Moreover, SC is an optimized impairments mitigation technique to overcome the effects of fading, shadowing and noise. This thesis presents ABER of BPSK, M-PAM and M-QAM modulation schemes analysis over MG shadowed fading channel under SC scheme in presence of GGD noise. A suitable shadowed fading channel known as MG for modeling fading and shadowing of EMNC-based BAN under CM1 scenario for NC has been considered. To mitigate the adverse effect of fading, shadowing and noise occur via body posture and surrounding variations of the body, SC diversity scheme has been used. So, the PDF of MG fading under dual SC scheme has been derived. Further, using CEP of the aforementioned modulation schemes over GGD noise and proposed PDF under SC ABER of various modulation schemes has been derived. In addition, similar analysis for ABER over WG shadowed fading channel has also been presented with dual SC scheme at BPSK and M-PAM modulation scheme under same noise model.
Keywords: ABER; Weibull-Gamma; Mixture-Gamma; GGD Noise